Real-time intrinsic fluorescence visualization and sizing of proteins and protein complexes in microfluidic devices - Challa, P; Peter, Q; Wright, M; Zhang, Y; Saar, K; Carozza, J; Benesch, J; Knowles, T (American Chemical Society, 2018)
Optical detection has become a convenient and scalable approach to read out information from microfluidic systems. For the study of many key biomolecules, however, including peptides and proteins, which have low fluorescence emission efficiencies at visible wavelengths, this approach typically requires labeling of the species of interest with extrinsic fluorophores to enhance the optical signal obtained - a process which can be time-consuming, requires purification steps, and has the propensity to perturb the behavior of the systems under study due to interactions between the labels and the analyte molecules. As such, the exploitation of the intrinsic fluorescence of protein molecules in the UV range of the electromagnetic spectrum is an attractive path to allow the study of unlabeled proteins. However, direct visualization using 280 nm excitation in microfluidic devices has to date commonly required the use of coherent sources with frequency multipliers and devices fabricated out of materials that are incompatible with soft lithography techniques. Here, we have developed a simple, robust, and cost-effective 280 nm LED platform that allows real-time visualization of intrinsic fluorescence from both unlabeled proteins and protein complexes in polydimethylsiloxane microfluidic channels fabricated through soft lithography. Using this platform, we demonstrate intrinsic fluorescence visualization of proteins at nanomolar concentrations on chip and combine visualization with micron-scale diffusional sizing to measure the hydrodynamic radii of individual proteins and protein complexes under their native conditions in solution in a label-free manner.